2017
DOI: 10.5511/plantbiotechnology.17.0615a
|View full text |Cite
|
Sign up to set email alerts
|

Inositol-requiring enzyme 1 affects meristematic division in roots under moderate salt stress in Arabidopsis

Abstract: The unfolded protein response (UPR) mitigates stress caused by accumulation of unfolded proteins in the endoplasmic reticulum (ER). Inositol-requiring enzyme 1 (IRE1) is the most conserved sensor of the UPR with ribonuclease activity that mediates cytoplasmic splicing and decay of mRNA encoding secretory and membrane proteins. In the present study, we demonstrate that the Arabidopsis mutant defective in two IRE1 genes exhibit retarded growth of primary roots under moderate salt stress, although such grow retar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Given the polyploid nature of the rapeseed genome, the gene content of the main QTL regions was analyzed to seek possible homoeology between the numerous QTLs. In some main QTL regions stable across N levels, BnaA06p33930 (At2g17520, INOSITOL REQUIERING ENZYME 1, IRE1) plays a role in the maintenance of root meristems under salt stress (Iwata et al 2017); BnaA07p31500 (At1g69588, CLAVATA3/ESR-RELATED 45, CLE45) could be involved in protophloem cells fate, thereby affecting root meristem growth (Depuydt et al 2013). In addition, some nitrate transporters were identi ed in main region Figure 3…”
Section: )mentioning
confidence: 99%
“…Given the polyploid nature of the rapeseed genome, the gene content of the main QTL regions was analyzed to seek possible homoeology between the numerous QTLs. In some main QTL regions stable across N levels, BnaA06p33930 (At2g17520, INOSITOL REQUIERING ENZYME 1, IRE1) plays a role in the maintenance of root meristems under salt stress (Iwata et al 2017); BnaA07p31500 (At1g69588, CLAVATA3/ESR-RELATED 45, CLE45) could be involved in protophloem cells fate, thereby affecting root meristem growth (Depuydt et al 2013). In addition, some nitrate transporters were identi ed in main region Figure 3…”
Section: )mentioning
confidence: 99%
“…Also, it has been reported that bZIP60 overexpression has a positive effect in plant tolerance to salt stress ( Fujita et al, 2007 ). Moreover, it has been recently reported that IRE1 also could play a role in plant response to salt stress, specifically in the maintenance of the root meristem under salt stress ( Iwata et al, 2017 ). Later, Babitha et al (2015) described that overexpression of bZIP60 from Finger millet ( Eleusine coracana L.) in tobacco plants enhanced tolerance to salt, osmotic, drought and chemical induced ER stress.…”
Section: Introductionmentioning
confidence: 99%